Optimising Telemedicine: Can it fulfil the right to healthcare in Indonesia? - Helena Primadianti Sulistyaningrum; Putu Samawati (Sriwijaya Law Review, 2026)
Telemedicine, an innovation in information technology-based healthcare services, has emerged as a solution to address the challenges of equitable and high-quality healthcare access. However, many challenges and obstacles still hinder the provision of telemedicine to the public. This study will examine two main points in addressing these challenges and obstacles: the sustainable benefits of telemedicine in fulfilling the right to health and the ideal legal reconstruction governing it. The legal issues analysed concern the lack of comprehensive regulations and the need for a clear legal framework to protect patient rights, ensure data security, and provide service certainty. The method employed is normative research, incorporating literature reviews and regulatory analysis, as well as ethical and legal concepts related to telemedicine. The analysis results indicate that telemedicine provides sustainable benefits through improved access to healthcare services, cost efficiency, and enhanced service quality and patient satisfaction, thereby fulfilling the right to health. However, without a strong legal foundation, telemedicine practices can pose significant legal risks, particularly regarding malpractice and data protection. Therefore, an ideal legal framework is needed to regulate aspects of the doctor-patient relationship, rights and obligations, data protection, and independent oversight mechanisms. Telemedicine is a solution and innovation that offers sustainable benefits in supporting the effective fulfilment of the right to health, provided it is accompanied by adequate legal protection to ensure justice, certainty, usefulness, safety, and quality in digital healthcare services.